2023
DOI: 10.37188/lam.2023.012
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric helical additive manufacturing

Abstract: 3D printing has revolutionized the manufacturing of volumetric components and structures for various fields. Thanks to the advent of photocurable resins, several fully volumetric light-based techniques have been recently developed to push further the current limitations of 3D printing. Although fast, this new generation of printers cannot fabricate objects whose typical size exceeds the centimeter without severely affecting the final resolution. Based on tomographic volumetric additive manufacturing, we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Models of dental retainers or lattice geometries featuring micron-sized details were among the first published examples using tomographic printing (Figure 11A,B). 33,41,152 Toombs et al recently demonstrated the fabrication of an auditory device which was suspended in a photoresin and subsequently overprinted to generate a composite object that fit the patient-specific shape of the ear canal (Figure 11C). 160 To avoid sedimentation of the suspended insert, an ethyl cellulose-based thermoreversible organogel photoresist was Cooling led to a rearrangement of intermolecular hydrogen bonds of ethyl cellulose, resulting in a porous solid network which trapped the TMPTA monomers.…”
Section: Chain Growth Cross-linking For Nonbiomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Models of dental retainers or lattice geometries featuring micron-sized details were among the first published examples using tomographic printing (Figure 11A,B). 33,41,152 Toombs et al recently demonstrated the fabrication of an auditory device which was suspended in a photoresin and subsequently overprinted to generate a composite object that fit the patient-specific shape of the ear canal (Figure 11C). 160 To avoid sedimentation of the suspended insert, an ethyl cellulose-based thermoreversible organogel photoresist was Cooling led to a rearrangement of intermolecular hydrogen bonds of ethyl cellulose, resulting in a porous solid network which trapped the TMPTA monomers.…”
Section: Chain Growth Cross-linking For Nonbiomedical Applicationsmentioning
confidence: 99%
“…111,186 Ingenious process design can also enable larger prints. For instance, larger prints in tomographic printing have been made possible by introducing a helical movement mechanism, 152 which allows indexing the vial position between tomographic projections to enable printing of constructs three times as large as those without a helical movement. One can envision such a system being controlled with a robotic arm, which could not only perform helical motions, but also print within multiple vials or within different regions of a single vial.…”
Section: Scaling Up the Build Volumementioning
confidence: 99%
“…included a motorized linear stage to have the resin follow a helical motion in the printer, enabling the fabrication of larger objects still in a layer-less manner. [ 38 ]…”
Section: D Printing As Tomographic Back-projectionmentioning
confidence: 99%
“…Objects printed in acrylates are typically stiff enough to retain their shape, but soft enough to open up new possibilities for elastomers, challenging materials to 3D print but with numerous industrial applications, like personalized hearing aids [ 12 ] or dental retainers [ 9 , 38 ] [Fig. 2 (a)].…”
Section: Materials Used For Vammentioning
confidence: 99%
“…Therefore, multi-material and multi-cell VBP is in urgent need [13,99]. The manufacture of organoids and large-scale tissue structures are hot topic applications [50,51]. Additionally, in situ VBP might be an interesting direction [100].…”
Section: Outlook and Future Perspectivesmentioning
confidence: 99%